2018
DOI: 10.20344/amp.8916
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Obesity – Are we Diagnosing with Appropriate Indicators?

Abstract: Introduction: We aim to define the iron deficiency prevalence and eventual differences between obese patients with and without metabolic syndrome. Material and Methods: Analysis of patients evaluated at multidisciplinary consultation of obesity in our institution between 2013 and 2015 (n = 260). Iron deficiency: ferritin levels < 15 ng/mL. Exclusion criteria: prior bariatric surgery; lack of ferritin or hemoglobin determinations. Results: We analyzed data from 215 patients (84.2% female) with a mean age of 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…No correlation between ID and obesity was found in eight studies which used a ferritin-based diagnosis (OR: 1.04, 95% CI: 0.69-1.56), whereas using nonferritin-based diagnosis, overweight and obese children were at 49% more risk of ID (OR: 1.49, 95% CI: 1.19, 1.85) [6]. ese findings are consistent with previous studies in adults which showed that ferritin-based diagnosis may have limitations for the diagnosis of ID in obese patients [33,34]. Similarly, in our study, which defined ID by using multiple markers including SF, we did not find any correlation between ID and overweight/ obesity.…”
Section: Discussionsupporting
confidence: 89%
“…No correlation between ID and obesity was found in eight studies which used a ferritin-based diagnosis (OR: 1.04, 95% CI: 0.69-1.56), whereas using nonferritin-based diagnosis, overweight and obese children were at 49% more risk of ID (OR: 1.49, 95% CI: 1.19, 1.85) [6]. ese findings are consistent with previous studies in adults which showed that ferritin-based diagnosis may have limitations for the diagnosis of ID in obese patients [33,34]. Similarly, in our study, which defined ID by using multiple markers including SF, we did not find any correlation between ID and overweight/ obesity.…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, obesity increases the risk of pregnancy-induced hypertension [9,32]. Obesity and smoking reduce iron concentrations [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical risk factors of pregnancy-induced hypertension [9,11] and influencing factors related to the concentration of iron [20,21] have been identified based on literature data.…”
Section: Methodsmentioning
confidence: 99%
“…Additional studies in non‐pregnant adults (or a mean age ≥18), not included in either Zhao et al (2015) or Cheng et al (2012), have conflicting results. Some studies suggest an association between obesity and ID, 71,74‐78 while multiple others note no difference 79‐82 …”
Section: Obesity and Red Blood Cell Countmentioning
confidence: 99%
“…Additional studies in non-pregnant adults (or a mean age ≥18), not included in either Zhao et al (2015) or Cheng et al (2012), have conflicting results. Some studies suggest an association between obesity and ID, 71,[74][75][76][77][78] while multiple others note no difference. [79][80][81][82] Given the literature, a relationship between obesity and ID likely exists in children and adolescents but remains unclear in adults.…”
Section: Sex Differencesmentioning
confidence: 99%